Strategic application of modular risk components to safely increase lung transplantation volume. Issue 9 (27th July 2020) - Pasrija, Chetan; Parchment, Nathaniel; Tran, Douglas; Mackowick, Kristen; Boulos, Francesca; Iacono, Aldo; Kim, June; Griffith, Bartley P.; Sanchez, Pablo G.; Pham, Si M.; Kon, Zachary N.
Abstract: Objectives: Considerable growth of individual lung transplant programs remains challenging. We hypothesized that the systematic implementation of modular risk components to a lung transplantation program would allow for expeditious growth without increasing mortality. Methods: All consecutive patients placed on the lung transplantation waitlist were reviewed. Patients were stratified by an 18‐month period surrounding the systematic implementation of the modular risk components Era 1 (1/2014‐6/2015) and Era 2 (7/2015‐12/2016). Modular risk components were separately evaluated for donors, recipients, and perioperative features. Results: One hundred and thirty‐two waitlist patients (Era 1: 48 and Era 2: 84) and 100 transplants (Era 1: 32 and Era 2: 68) were identified. There was a trend toward decreased waitlist mortality ( P  = .07). In Era 2, the use of ex vivo lung perfusion ( P  = .05) and donor‐recipient over‐sizing ( P  = .005) significantly increased. Moreover, transplantation with a lung allocation score greater than 70 ( P  = .05), extracorporeal support ( P  = .06), and desensitization ( P  = .008) were more common. Transplant rate significantly improved from Era 1 to Era 2 (325 vs 535 transplants per 100 patient years, P  = .02). While primary graft dysfunction (PGD) grade 3 at 72 hours ( P  = .05) was significantly higher in Era 2, 1‐year freedom from rejection was similar (86% vs 90%, P  = .69) and survival (81% vs 95%, P  = .02) was significantly greater in Era 2. Conclusions: The systematic implementation of a modular risk components to a lung transplantation program can result in a significant increase in center volume. However, measures to mitigate an expected increase in the incidence of PGD must be undertaken to maintain excellent short and midterm outcomes.